Make me more comfortable: effects of a hypnosis session on pain perception in chronic pain patients - Ogez, David; Landry, Mathieu; Caron-Trahan, Rémi; Jusseaux, Anne-Eva; Aubin, Maryse; Véronneau, Jade; Fournier, Valentyn; Godin, Nadia; Idrissi, Moulay; Rainville, Pierre; Richebé, Philippe (Frontiers in Psychology, 2024)
Approximately one-quarter of Canadians experience chronic pain, a debilitating condition often necessitating opioid use, which raises concerns regarding dependency and overdose risks. As an alternative, we developed the HYlaDO program (HYpnose de la DOuleur, hypnosis of Pain in french), a novel self-hypnosis approach for chronic pain management.The development of this program followed the ORBIT model, a comprehensive framework for designing interventions encompassing several phases ranging from design to efficacy assessment. In the present work, we conducted a preliminary evaluation of the HYlaDO program with 21 participants (18 of the 21 patients were included in the analysis). The primary objective was to determine one session of the program's effectiveness in altering pain, anxiety and relaxation via pre-post analysis. The secondary goal was to examine the long-term effects across the same measures, in addition to the overall quality of life. The results highlight the benefits of our approach, while participants reported short-term significant pain reduction, decreased anxiety, and increased relaxation. Additionally, preliminary trends suggest improvements in physical activity and quality of life metrics. These positive outcomes highlight HYlaDO's potential as an alternative to opioid therapy for chronic pain. Encouraged by these results, we aim to extend our research to a broader and more diverse cohort, paving the way for comprehensive randomized controlled trials. This expansion will further validate HYlaDO's efficacy and its role in transforming chronic pain management.